FOLK RITUAL TO ARTISTIC PERFORMANCE: CHANGING TERRAINS OF THIRAYATTAM - Mathew, Maria Lisa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Thirayattam is an ethnic ritual art form of Sothern Malabar region of Kerala, India. It is enacted in the courtyard of sacred groves or “Kaavukal” and village temples of Kozhikode and Malappuram regions between January and April. This divine dance drama is a harmonious blend of dance, songs, instrumental music, martial arts, facial and bodily makeup and rituals. This ethnic folk art is enacted to please the deities using its own typical customs and performance style. Rituals and performances once seen as contradictory have now become complementary to each other due to the changing circumstances of the present era. The current article attempts to trace the transition of this ritualistic folk art to an independent art form in the 21st century. In 2022, P. V. Sadique a trainer in Mappila arts, from Kozhikode performed Thirayattam at a film award ceremony in Kochi. With his performance, the ritualistic performance now gained a secular avatar breaking the long prevailing caste and class norms. The article also ponders upon how Thirayattam performance by Seeta Sathish broke the gender, and caste barriers associated with this art form. On a deeper analysis, it was revealed that the current change was the result of the long-standing efforts of practitioners and academicians to preserve this art form for future generations. The folk ritual which was on the verge of extinction got a new lease of life with its transition to a more secular and popular space.